Improving Warehousing And Inventory Management At Teaching Factory Electronic Manufacturing - Budiman; Nikita Dwi Utami Prima Putri; Annisa Rizqia Rahmadani; Rizky Afdhal; Ilham Ahmad Dani; Yulinda; Fandy Bestario Harlan; Adhitomo Wirawan; Alrido Martha Devano (Journal of Collaborative Industrial Management (JCIM), 2025)
Effective inventory management is essential to reduce financial losses and maintain the integrity of the production and supply system. The core of this management lies in the organized management of inventory and distribution, collectively known as inventory management. By following standard operating procedures (SOPs), this approach ensures that warehouse operations are streamlined and run according to established guidelines.  Avoiding the loss of goods is critical not only for economic reasons, but also to avoid disruptions in the warehouse and production and delivery processes. Storage management acts as a safeguard against these potential failures. The term encompasses various strategies and practices aimed at optimizing the storage, retrieval and distribution of goods in a warehouse environment. In essence, the emphasis on inventory management is a proactive measure to improve operational efficiency. This involves careful planning and execution and alignment with SOPs to maintain consistency and reliability of warehouse operations. With this approach, companies can not only avoid financial losses associated with misplaced or damaged products, but also promote a smooth workflow in the warehouse.   The key to successful warehouse management lies in its ability to combine best practices, technology and adherence to established procedures. This ensures that the warehouse is operating at  full capacity and meeting production targets and delivery schedules. Ultimately, the synergy between efficient inventory management and SOP adherence forms a solid framework for continued operational success in the dynamic field of warehousing and distribution.